Accurate and efficient solution of electromagnetic scattering from randomly rough surface using MoM‐SMCG with adaptive quadrature. Issue 18 (21st May 2021) - Du, Yanlei; Yin, Junjun; Li, Xiang; Gao, Fan; Yang, Jian
Abstract: An adaptive quadrature method is proposed and implemented with the full‐wave MoM‐SMCG to accurately and efficiently solve the electromagnetic scattering from randomly rough surfaces. Without using high‐order basis functions and dense surface discretisation, high numerical accuracy of computing the inner integrals for near‐field impedance matrix elements is ensured by exploiting the orthogonal Legendre polynomials. Far‐field interactions are calculated using the acceleration algorithms and the iterative solver to archive reasonable computational complexity and memory consumption. The proposed method is validated on solving the electromagnetic scattering and emission from rough ocean surfaces with fine‐scale roughness and large dielectric constants. By comparing to the existing methods, simulation results indicate the proposed method has high computational efficiency and memory saving with also maintaining good accuracy.